Institutional dimensions and entrepreneurial activity: An international study (2014)
The purpose of this article is to examine the influence of institutional dimensions (regulative, normative and cultural-cognitive) on the probability of becoming an entrepreneur. The main findings demonstrate, through logistic regression, that a favourable regulative dimension (fewer procedures to start a business), normative dimension (higher media attention for new business) and cultural-cognitive dimension (better entrepreneurial skills, less fear of business failure and better knowing of entrepreneurs) increase the probability of being an entrepreneur. Data were obtained from both the Global Entrepreneurship Monitor and the International Institute for Management and Development for the year 2008, considering a sample of 30 countries and 36,525 individuals. The study advances the literature by providing new information on the environmental factors that affect entrepreneurial activity in the light of institutional economics. Also, the research could be useful for designing policies to foster entrepreneurship in different environments. © 2013 Springer Science+Business Media New York.